Prenatal diagnosis of coarctation of the aorta improves survival and reduces morbidity. Issue 1 (1st January 2002) - Franklin, O; Burch, M; Manning, N; Sleeman, K; Gould, S; Archer, N
Abstract : Objective: To investigate whether antenatal diagnosis of coarctation of the aorta results in reduced mortality and improved preoperative haemodynamic stability compared with postnatal diagnosis. Design: Retrospective review of all cases of coarctation of the aorta presenting to a tertiary fetal and neonatal cardiology service from January 1994 to December 1998. Methods: Prenatal, postnatal, and necropsy records were reviewed to determine survival in the two groups. Markers of preoperative illness severity were recorded, including presence of femoral pulse, collapse, left ventricular function, ductal patency on echocardiography, coagulation status, duration of intensive care unit and total hospital stay, heart rate, respiratory rate, plasma creatinine, plasma potassium, and right upper limb blood pressure. A univarate and multivariate analysis was conducted on all variables and a cumulative score was created and subjected to logistic regression analysis. Results: Both collapse and death were more common in the postnatally diagnosed group (p < 0.05). Femoral pulses were more likely to be palpable and there was echocardiographic evidence of duct patency in the antenatally diagnosed infants (p < 0.001 and p < 0.05, respectively). An increased respiratory rate was associated with postnatal presentation (p < 0.05). Infants with haemodynamic instability preoperatively were more likely to have been diagnosed postnatally (p < 0.01). Conclusions: Antenatal diagnosis of coarctation of the aorta is associated with improved survival and preoperative clinical condition.